What do Indigenous education policy frameworks reveal about commitments to reconciliation in Canadian school systems? - Wotherspoon, Terry; Milne, Emily (My University, 2020)
The national Truth and Reconciliation Commission of Canada has challenged governments and school boards across Canada to acknowledge and address the damaging legacies of residential schooling while ensuring that all students gain an adequate understanding of relations between Indigenous Peoples and non-Indigenous peoples. This article explores the dynamics and prospects for effective change associated with reforms in elementary and secondary education systems since the release of the Commission’s Calls to Action, focusing on the policy frameworks employed by provincial and territorial governments to guide these actions. The analysis examines critically the overt and hidden messages conveyed through discourses within policy documents and statements. The key questions we address include: What do current education policy frameworks and actions regarding Indigenous Peoples reveal about government approaches to education and settler–Indigenous relationships in Canada? To what extent is effective reconciliation possible, and how can it be accomplished in the context of institutional structures and discourses within a White settler colonial society? The findings reveal that substantial movement towards greater acknowledgement of Indigenous knowledge systems and incorporation of Indigenous content continues to be subordinated to or embedded within Western assumptions, norms, and standards.
Keywords: education policy; Indigenous education; reconciliation; Truth and Reconciliation Commission of Canada